2011
DOI: 10.1039/c1md00155h
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and antiproliferative activity of urocanic-chalcone hybrid derivatives

Abstract: Inspired by biologically active natural products, a hybrid analogue that combines the N-Me urocanic side chain of the sarcodictyin family of compounds with the chalcone motif has been proposed, synthesised and examined for antiproliferative activity in three cancer cell lines and one normal primary cell line. The analogues are all synthesised in one or two steps from commercially available materials and, of the compounds examined, the proposed hybrid analogue displays the most active and selective inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…26 The effect of an N-benzoyl substituent (8h) was also investigated and exhibited no observable antiproliferative activity in the two cell lines examined (entry 8, Table 1). Following our previous studies using 3,4,5-trimethoxyphenyl substituents, 31 which have been shown to play crucial roles in activity, [32][33][34][35][36] we investigated this substitution pattern in the N-benzoyl group. Remarkably, the corresponding 3,4,5-trimethoxybenzoyl derivative 8i displayed potent activity and selectivity for the highly metastatic human breast carcinoma (MDA-MB-231, entry 9).…”
Section: Resultsmentioning
confidence: 99%
“…26 The effect of an N-benzoyl substituent (8h) was also investigated and exhibited no observable antiproliferative activity in the two cell lines examined (entry 8, Table 1). Following our previous studies using 3,4,5-trimethoxyphenyl substituents, 31 which have been shown to play crucial roles in activity, [32][33][34][35][36] we investigated this substitution pattern in the N-benzoyl group. Remarkably, the corresponding 3,4,5-trimethoxybenzoyl derivative 8i displayed potent activity and selectivity for the highly metastatic human breast carcinoma (MDA-MB-231, entry 9).…”
Section: Resultsmentioning
confidence: 99%
“…Further, tubulin-targeting compounds including taxanes, vinca alkaloids, and combretastatins have been widely used in the treatment of many cancers [111,112]. The poor bioavailability and multidrug resistance of these drugs compel researchers to exploit novel inhibitors toward microtubule polymerization with low side effect, little drug resistance, and good oral activity [113,114].…”
Section: Bta As Microtubule Polymerization Inhibitorsmentioning
confidence: 99%
“…Therefore, the discovery of potential microtubule inhibitors is an attractive strategy for cancer therapy. Although tubulin‐targeting compounds including taxanes, vinca alkaloids, and combretastatins have been widely used in the treatment of many cancers, the poor bioavailability and multidrug resistance of these drugs compel researchers to exploit novel inhibitors toward microtubule polymerization with low side effect, little drug resistance, and good oral activity . The structures for imidazoles as microtubule polymerization inhibitors are shown in Figure .…”
Section: Imidazoles As Anticancer Agentsmentioning
confidence: 99%